2018
DOI: 10.1186/s13048-018-0383-2
|View full text |Cite
|
Sign up to set email alerts
|

Precise preoperative diagnosis of struma ovarii with pseudo-Meigs’ syndrome mimicking ovarian cancer with the combination of 131I scintigraphy and 18F–FDG PET: case report and review of the literature

Abstract: BackgroundStruma ovarii is a rare ovarian neoplasm that often appears malignant on conventional imaging. Pseudo-Meigs’ syndrome with ascites, pleural effusion, and elevated serum CA 125 levels is much rarer and leads to misdiagnosis of ovarian cancer and unnecessary extended surgery.Case presentationA 50-year-old woman with abdominal distention and dyspnoea was referred to our hospital. Ultrasound, computed tomography (CT), and magnetic resonance imaging (MRI) showed a polycystic ovarian tumor with a solid com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 50 publications
0
24
1
Order By: Relevance
“…Ovarian teratomas are the most common germ cell tumors and represent ∼20% of all ovarian tumors (1); these tumors contain tissue from the three germ layers, typically including hair, skin, bone, and thyroid tissue. Struma ovarii is a rare form of ovarian teratomas, are composed of more than 50% thyroid tissue (2), and account for about 2% to 5% of ovarian teratomas and 0.5 to 1% of all ovarian tumors (3)(4)(5). Between 5 and 10% of struma ovarii cases are defined as MSO by the World Health Organization (WHO) and are histologically identified to differentiate from thyroid carcinomas (6).…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian teratomas are the most common germ cell tumors and represent ∼20% of all ovarian tumors (1); these tumors contain tissue from the three germ layers, typically including hair, skin, bone, and thyroid tissue. Struma ovarii is a rare form of ovarian teratomas, are composed of more than 50% thyroid tissue (2), and account for about 2% to 5% of ovarian teratomas and 0.5 to 1% of all ovarian tumors (3)(4)(5). Between 5 and 10% of struma ovarii cases are defined as MSO by the World Health Organization (WHO) and are histologically identified to differentiate from thyroid carcinomas (6).…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] A definitive diagnosis of Meigs syndrome or PMS can only be made in retrospect following the resolution of fluid accumulations after removing the ovarian tumor. [ 19 ] It is of clinical significance to use these syndromes as the differential diagnosis of pleural effusion, especially in young women who desire fertility or pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…The large tumor size, abundant adhesions, and ovarian serosal defects are high-risk features of struma ovarii that may be associated with aggressive behaviors (1,8). Mildly elevated CA-125 levels are found in up to 30% of these tumors, although in the presence of ascites, this level may be higher (1,9). Case reports have shown that higher levels of CA-125 were associated with a higher volume of ascites; however, the size of the tumor was not linearly correlated with the CA-125 level (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is non-specific and generally contains solid components or thick septa in the cystic component similar to an ovarian malignancy (1,7). On the other hand, successful preoperative diagnosis of a struma ovarii, associated with pseudo-Meigs' syndrome, has been reported using a combination of 18F-FDG PET/CT and 131I scintigraphy (9). These tumors are classically unilateral, and less than 1% of them are reported to be bilateral.…”
Section: Discussionmentioning
confidence: 99%